Atypical clinical and laboratory features of fish-tank granuloma: A case report - Sander, Michael (SAGE Open Med Case Rep, 2018)
We report a case of cutaneous Mycobacterium marinum infection with the unusual reported features of pruritus and paresthesia. In addition, we report a lack of in-vivo response to antibiotics based on in-vitro susceptibility testing.